2014
DOI: 10.1080/09540121.2014.911809
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and its association with HIV risk behaviors among a cohort of patients attending HIV clinical care in Tanzania, Kenya, and Namibia

Abstract: This article describes the frequency of alcohol use among HIV-positive patients attending clinical care in sub-Saharan Africa and explores the association between alcohol use, medication adherence, and sexual risk behavior. Data from 3538 patients attending an HIV clinic in Kenya, Tanzania, or Namibia were captured through interview and medical record abstraction. Participants were categorized into three drinking categories: nondrinkers, nonharmful drinkers, and harmful/likely dependent drinkers. A proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 45 publications
2
32
1
Order By: Relevance
“…Drinking alcohol was significantly associated with sub-optimal adherence according to self-report. This is in agreement with previous study findings in both resource-limited and resourcerich settings (Conen et al, 2009;Medley et al, 2014), and it might be related to forgetfulness to take ARV drugs on time or inability to strictly follow the refill appointment schedules as a result of drinking. Therefore, interventions aimed at tackling sub-optimal adherence should consider improving social support and limiting alcohol intake as potential program targets.…”
Section: Discussionsupporting
confidence: 83%
“…Drinking alcohol was significantly associated with sub-optimal adherence according to self-report. This is in agreement with previous study findings in both resource-limited and resourcerich settings (Conen et al, 2009;Medley et al, 2014), and it might be related to forgetfulness to take ARV drugs on time or inability to strictly follow the refill appointment schedules as a result of drinking. Therefore, interventions aimed at tackling sub-optimal adherence should consider improving social support and limiting alcohol intake as potential program targets.…”
Section: Discussionsupporting
confidence: 83%
“…In another research conducted in sub-Saharan Africa, including Kenya, Tanzania and Namibia countries, the association between alcohol users and risky sexual behavior in people living with HIV was evaluated. The same highlights the need to integrate alcohol counseling in routine monitoring in people living with HIV/Aids (22) . Given the many intersections between alcohol and HIV, it is necessary the implementation of policies focusing on reducing alcohol consumption and risk behavior.…”
Section: Discussionmentioning
confidence: 99%
“…They found that highest level of drinking, harmful/likely dependent, was associated with inconsistent condom use, and other high risk behaviors. Binge drinking was also associated with inconsistent condom use [13]. …”
Section: Introductionmentioning
confidence: 99%